Changes in Appetite-Dependent Hormones and Body Composition After 8 Weeks of High-Intensity Interval Training and Vitamin D Supplementation in Sedentary Overweight Men - Sheikholeslami-Vatani, Dariush; Rostamzadeh, Naser (Frontiers in Nutrition, 2022)
Exercise and diet are important factors for energy balance and appetite regulation. The aim of this study was to investigate the effect of eight weeks High Intensity Interval Training (HIIT) and vitamin D3 supplementation in sedentary overweight men. 48 participants were randomly assigned to one of the following four groups (n=12):HIIT+VitD, HIIT+placebo (3 sessions per week, 10 x 1 min interval cycling at 90 -100 % VO2peak separated by 1 min active recovery at 15 % VO2peakfor eight weeks), Vit D and control groups. Participants received 2000 IU/day 25(OH)D3 or placebo. Measurements were taken pre and post training after 10 hours overnight fasting. Insulin, weight, BMI and body fat percentage were significantly decreased, but PYY was significantly increased in the HIIT+ Vit D and HIIT+ placebo groups (p=0.001 and p=0.001, respectively) after 8 weeks of HIIT. Insulin (p=0.009, p=0.001), weight, BMI and body fat percentage (p=0.001, p=0.001) were significantly lower in the HIIT+Vit D and HIIT+ placebo groups compared to the Vit D and control groups. However, PYY was significantly higher in the HIIT+Vit D group compared to the Vit D (p=0.025) and control groups (p=0.007) and also in the HIIT+placebo group compared to the Vit D (p=0.037)and control groups (p=0.032) after 8 weeks of HIIT. The combination of regular HIIT with vitamin D supplementation has a effect on appetite control and body composition.